2013
DOI: 10.1152/ajprenal.00182.2012
|View full text |Cite
|
Sign up to set email alerts
|

Chronic interstitial fibrosis in the rat kidney induced by long-term (6-mo) exposure to lithium

Abstract: There is a lack of suitable animal models that replicate the slowly progressive chronic interstitial fibrosis that is characteristic of many human chronic nephropathies. We describe a chronic long-term (6-mo) model of lithium-induced renal fibrosis, with minimal active inflammation, which mimics chronic kidney interstitial fibrosis seen in the human kidney. Rats received lithium via their chow (60 mmol lithium/kg food) daily for 6 mo. No animals died during the exposure. Nephrogenic diabetes insipidus was esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 32 publications
4
39
4
Order By: Relevance
“…Kidney damage in humans and rodents chronically treated with lithium is mostly characterized by proximal tubular atrophy and chronic interstitial fibrosis (Table 1). [69][70][71][72] Some lithium-treated patients also display glomerulosclerosis, but animal studies revealed that this pathology occurs after the onset of interstitial fibrosis and tubular atrophy. 7,69,[72][73][74][75] Although this suggests that glomerulosclerosis results from damage at other renal segments, it probably constitutes an essential step in the final progression to ESRD.…”
Section: Esrdmentioning
confidence: 99%
See 2 more Smart Citations
“…Kidney damage in humans and rodents chronically treated with lithium is mostly characterized by proximal tubular atrophy and chronic interstitial fibrosis (Table 1). [69][70][71][72] Some lithium-treated patients also display glomerulosclerosis, but animal studies revealed that this pathology occurs after the onset of interstitial fibrosis and tubular atrophy. 7,69,[72][73][74][75] Although this suggests that glomerulosclerosis results from damage at other renal segments, it probably constitutes an essential step in the final progression to ESRD.…”
Section: Esrdmentioning
confidence: 99%
“…[69][70][71][72] Some lithium-treated patients also display glomerulosclerosis, but animal studies revealed that this pathology occurs after the onset of interstitial fibrosis and tubular atrophy. 7,69,[72][73][74][75] Although this suggests that glomerulosclerosis results from damage at other renal segments, it probably constitutes an essential step in the final progression to ESRD. 76 Other than these pathologic features, histology on biopsies or magnetic resonance imaging scans revealed that a number of lithium-treated patients also displays renal microcysts.…”
Section: Esrdmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32] The consequences of such a prolonged G2 cell cycle arrest are not fully understood, although recent investigations of different AKI models indicate that activation of c-Jun NH 2 -terminal signaling in G2-arrested cells can lead to renal fibrosis due to the upregulation of profibrotic cytokines, including TGF-b1. 24 Because fibrosis and CKD are also observed after long-term lithium treatment, 33 and lithium has been shown to activate c-Jun NH 2 -terminal signaling 16 and stimulate TGF-b1 production in the collecting duct, 33 the role of G2-arrested cells in lithium-induced fibrosis should be further investigated.…”
Section: Lithium Enhances G1/s Cell Cycle Progressionmentioning
confidence: 99%
“…There are about 10% of the general adult population affected by CRF worldwide, which is often complicated by sepsis and cardiovascular disease [4]. Previous study has revealed that CRF is characterized by slowly progressive chronic renal interstitial fibrosis (RIF) and accompanied with increased oxidative stress (OS) that is already found in the early stage of renal disease [5]. Although a low protein diets is the effective treatment regimen for CRF, the side effects of this strategy cannot be ignored, such as a probable occurrence of proteinuria and functional impairment [6].…”
Section: Introductionmentioning
confidence: 99%